The Effect Of User Experience, Ease Of Service, And Comfort Of Service On Return Visit Interest With User Satisfaction As An Intervening Variable - Isnia, Aulia Nuril; Qomariah, Nurul; Hermawan, Haris (UNIVED Press, 2026)
This research investigates how user experience, service convenience, and service comfort affect revisit intention, with user satisfaction positioned as a mediating variable within the Legal Metrology Unit of Banyuwangi Regency. A quantitative method with an explanatory research design was applied to explore these relationships. The study population comprised 245 users or entrepreneurs, from which 152 respondents were purposively selected as the sample. Data analysis was carried out using Structural Equation Modeling (SEM) assisted by WarpPLS 8.0 software to test the proposed model and hypotheses. The results indicate that user experience, service convenience, and service comfort have an effect on user satisfaction and revisit intention. Furthermore, user satisfaction has an effect on revisit intention and mediates the influence of user experience, service convenience, and service comfort on revisit intention. These findings suggest that the more positive the user's experience, the more convenient and comfortable the service, the higher the satisfaction level, which in turn encourages users to revisit the service. Practically, the results provide implications for the management of the Legal Metrology Unit to maintain and enhance service quality through clear information, simplified procedures, improved physical comfort, and strengthened positive social interactions.